Concordance for hypoplastic left heart syndrome in a monochorionic twin pregnancy. Issue 4 (1st April 2003) - Andrews, R E; Cook, A C; Yates, R W M
Abstract : The risk of structural heart disease is significantly higher in twin pregnancies than in singleton pregnancies, but the concordance rate has been found to be relatively low, even in monochorionic pregnancies. This is the first report of a monochorionic twin pregnancy concordant for hypoplastic left heart syndrome (HLHS), the diagnosis having been made by fetal echocardiography at 15 weeks' gestation. The findings were confirmed at necropsy at 17 weeks' gestation, following termination of pregnancy. Both twins had mitral and aortic atresia, with severely hypoplastic aortic arches. This report adds weight to there being a genetic component to the cause of HLHS in some cases and illustrates how the findings from early fetal echocardiography with postmortem follow up can help to extend the understanding of the aetiology of this condition.